Learner engagement, retention and success: why size matters in massive open online courses (MOOCs). (2nd January 2020) - Padilla Rodriguez, Brenda Cecilia; Armellini, Alejandro; Rodriguez Nieto, Ma Concepción
ABSTRACT: Massive open online courses (MOOCs) are usually six to ten weeks long. Participation tends to decrease as the courses progress, leading to low completion rates. This led to the question: Could shorter MOOCs contribute to learners' engagement, retention and success? This paper compares two versions of Study Skills MOOC, which shared the same content but were delivered in different length formats. One was deployed as a single six-week course and the other as two three-week blocks. In total, 617 people registered for the two versions. Data sources included learning analytics, surveys and the Spanish version of the General Self-Efficacy Scale. Both versions of the Study Skills MOOC resulted in increased participants' self-efficacy. However, learners enrolled in the version composed of two three-week blocks were also more engaged with course content, other students and the facilitators. Their retention and completion rates were higher than those in the longer version of the course. Reasons linked to goal proximity, motivation, interactions and social modelling are discussed